SOLAR ENERGY: A POTENTIAL SOURCE OF RENEWABLE AND CLEAN ENERGY - Aryal, Deepak (International Journal of Research -GRANTHAALAYAH, 2018)
This paper reports analytical review results on the global and national importance of solar energy as a clean and renewable source of energy. Pre-monsoon and post monsoon seasons have higher mean monthly sunshine duration (about 8 hours/day) than summer (about 5 hours/day) and winter (about 7 hours/day) seasons in Kathmandu. The lowest sunshine duration during summer season is attributed to the effect of monsoonal clouds during that period. Pre-monsoon and monsoon seasons receive solar energy of about 250 W/m2 and 200 W/m2 respectively. The winter season receives the least amount of solar radiation (about 150 W/m2). Results show high prospect of solar energy utilization both in rural and urban areas of Nepal.